Pelatihan LLS (Language Learning Strategies) Untuk Pelajar Sekolah Menengah Nagari Tanjung Balik, Solok-SUMBAR - Syaifullah; Hamuddin, Budianto; Ahmad, Arif (IKHLAS: Jurnal Pengabdian Dosen dan Mahasiswa, 2025)
Based on the results of an interview via WA with one of the vice principals there, he said that our students have not achieved any achievements from English activities or competitions. Likewise, when viewed in daily life or in Teaching and Learning Activities (KBM), their English skills are still very standard. Related to the initial data above, the FADIKSI-UNILAK PKM Team chose the Tanjung Balik village as a partner to be a target in the Tridarma of higher education, especially community service with the title "LLS (Language Learning Strategies) Training for High School Students in the Tanjung Balik Village Solok-SUMBAR). This activity was carried out on December 17-19, 2025 which was attended by 40 students and 4 teachers. After the PKM Team shared English learning strategies, according to a report from one of the teachers, this activity was very positive because after observing it, the students began to have motivation and enthusiasm to learn English.